"I miss the care even though I know it's just a machine": An explorative study of the relationship between an Internet-based smoking cessation intervention and its participants. (September 2013) - Brandt, Caroline L; Dalum, Peter; Thomsen, Tine T
This study aimed to investigate how users perceive the different elements of an internet based smoking cessation intervention and to see if the program meet needs and expectations of people in a smoking cessation process. Nine semi-structured interviews were conducted in February 2010. Participants were recruited via the homepage of the smoking cessation program Dit Digitale Stopprogram (Your Digital Quit Program) operated by the Danish Cancer Society. The main result was that participants established a relationship to the program which influenced their smoking cessation process. Participants perceived the program as caring and found it supportive. However, the program also created feelings of frustration, disappointment and anger. Some participants in the last phase of cessation experienced text messages from the program as smoking cues. The study concluded that individual interpretations of the different elements in an Internet-based smoking cessation intervention can have both positive and negative impact on the smoking cessation process of participants.